A Study on Mobile Based Nbfc Catering Towards Rural Indian Customers – Special Reference To Igatpuri in Maharastra - P. S. Aithal, Abdul Khalid (Journal of Neonatal Surgery, 2025)
This study is an attempt to find the impact & usage of Mobile application financial services need of rural customers, it is intrinsic to economic development that in developing countries, the tendency has been to think of a finance as a basic right, comparable to drinking water, health etc. While access to finance may be a critical factor for many households to hoist themselves out of poverty, it is not necessary that access must come from a relationship with help of technology , data science and Machine learning based rule engine platform tightly coupled with mobile application. This study is to show how mobile based applications are helping in rural Indian despite of that infrastructural constraints like electricity, transportation and Infrastructure Becomes hurdle for getting financial needs for rural India. Major public sector banks are not present in rural India, in this scenario NBFC (Non-Banking Financial Corporation) has to serve to financial needs due to electricity and power systems are having challenges to serve to customers, alternate solution to this problem is mobility. stack of mobility comes into picture which plays a vital role becomes bridge between NBFC and Customer.